2020
DOI: 10.2991/jegh.k.200117.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Insomnia Among a Representative Sample of the Lebanese Population: Results of a Cross-Sectional Study

Abstract: The objectives of the study were to identify the prevalence of insomnia among a representative sample of the Lebanese population and to assess potential factors associated with insomnia among this group. A cross-sectional study was done in the Lebanese population from August 2017 to April 2018 enrolling 789 participants using a proportionate random sample from all five Lebanese governorates. Participants filled a self-administered Arabic questionnaire. The Athens Insomnia Scale was used to diagnose insomnia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Furthermore, in the current study the participants who were divorced/widowed they have 3.09 times higher risk or probability of experiencing insomnia. This results support with many publish research ( Necho et al, 2020 , Alkhatatbeh et al, 2020 , Al Karaki et al, 2020 ). Our study also reported that those medical clinical students living in hostels during the COVID pandemic they have more insomnia (1.23 times higher) as compared to others variables.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in the current study the participants who were divorced/widowed they have 3.09 times higher risk or probability of experiencing insomnia. This results support with many publish research ( Necho et al, 2020 , Alkhatatbeh et al, 2020 , Al Karaki et al, 2020 ). Our study also reported that those medical clinical students living in hostels during the COVID pandemic they have more insomnia (1.23 times higher) as compared to others variables.…”
Section: Discussionsupporting
confidence: 92%
“…Those with dementia (according to one of the family members) were excluded from the study. The methodology used in this study is similar to the one used in previous paper 28‐48 …”
Section: Methodsmentioning
confidence: 99%
“…These factors cause a lack of economic growth, low job creation and lead to social problems (aggression and violence) [33]. They can have a negative impact on Lebanese adolescents that consequently face secondary emotional stress, leading to more mental health problems such as insomnia [34], anxiety [35], depression [36], and alexithymia [37]. To our knowledge, there is a lack of research about alexithymia among adolescents in Lebanon.…”
Section: Open Accessmentioning
confidence: 99%